2020
DOI: 10.47391/jpma.703
|View full text |Cite
|
Sign up to set email alerts
|

Fodder cutter (Tokka) injuries; a preventable morbidity

Abstract: Abstract Pakistan is an agricultural country where fodder cutter (Tokka) is a commonly used machine on the farms. While using it, farmers often meet with accidents causing injuries which are disastrous, and mainly involve the young generation often causing lifelong disability. This is a hospital-based case series, conducted from June 2018 to January 2019 in the Department of Surgery, Lahore General Hospital, Lahore. For this study the patient’s demographic data, site of injury, procedure performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The findings from our study showed that male persons aged between 21 and 40 years were the commonest group of workers likely to sustain chaff cutter injuries involving the hand. In a study from Pakistan including 30 cases of tokka (chaff cutter) injuries, the male-to-female ratio of the victims was 3:1 ( Ali et al, 2021 ). In contrast, in another retrospective study from Pakistan, Naseer et al (2016) found that male persons were affected in only 43.8% of the cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings from our study showed that male persons aged between 21 and 40 years were the commonest group of workers likely to sustain chaff cutter injuries involving the hand. In a study from Pakistan including 30 cases of tokka (chaff cutter) injuries, the male-to-female ratio of the victims was 3:1 ( Ali et al, 2021 ). In contrast, in another retrospective study from Pakistan, Naseer et al (2016) found that male persons were affected in only 43.8% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…The use of farm machinery such as hay bailers and chaff cutters has been implicated as the commonest cause of hand injury ( Naseer et al , 2016 ) Chaff cutters are used in chopping of fodder in dairy farming. Whereas the traditional chaff cutters were manually operated and safe, current cutters in use are power driven and more unsafe ( Naseer et al , 2016 ; Ali et al, 2021 ). Increasing mechanization predisposes workers to high risks for injuries, often with devastating outcomes ( Angoules et al , 2007 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation